The Need to Develop the Behavior of Orphan Children (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article presents scientific theoretical information on the social necessity of developing social behavior in foster children of orphanages, as well as a partial analysis of the results obtained in the research process.